The lion of Kotte : his life & times - Raṇasiṃha, Ḍaglas Bī (Ranasinghe, 1976)
Compilation of documents depicting the life and service of Edward Walter Perera, 1875-1953, Ceylonese statesman and activist in the freedom movement; v.1: chiefly comprises documents pertaining to the 1915 communal disturbances in Ceylon.